Antinociceptive and anti-inflammatory effects of thiamine in Long Evans rats - Ainan, Sayema; Begum, Noorzahan; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2016)
Background: Thiamine along with other B vitamins has been prescribed since long for treatment of various painful conditions, though individual effects of thiamine on nociception and inflammation are yet to be clearly demonstrated. Objective: To assess the effects of increasing doses of thiamine supplementation against pain and inflammation. Methods: This experimental study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from March 2014 to February 2015. Total twenty four male Long Evans rats weighing (200±20 gm) were treated with three different doses of thiamine hydrochloride (THCL 100, 200, 250, mg/kg/day; experimental) or normal saline (5 ml/kg/day; control) intraperitoneally for 7 consecutive days. To evaluate the thiamines effect on nociceptive pain, early phase (0-5 minutes) and on inflammatory pain, late phase (16-60 minutes) of the formalin test, were observed. In both phases, total frequency of jerking and total duration of flexing and licking of the right hind paw were counted after administration of subcutaneous formalin (50 ?l, 2.5%) injection. After formalin test, all the rats were also subjected to formalin induced paw edema test using a water plethysmometer to observe the antiinflammatory effect of thiamine. Statistical analysis was done by ANOVA, followed by Bonferroni post hoc test. In the interpretation of results, p?0.05 was considered as significant. Results: In formalin test, thiamine lowered frequency of jerking (after all 3 doses, in both phases) and duration of flexing and licking (200 mg/kg - p<0.001, in late phases; 250 mg/kg (p<0.001), in both phases) significantly. Additionally, thiamine lowered paw edema significantly (p<0.001) in higher 2 doses. Conclusion: This study concludes that, thiamine may have dose dependent antinociceptive and anti-inflammatory effects. Bangladesh Soc Physiol. 2016, June; 11(1): 6-12